Pemenuhan Hak Atas Kesehatan melalui Badan Penyelenggara Jaminan Sosial Kesehatan di Indonesia - Insan Firdaus (Badan Strategi Kebijakan Hukum, 2014)
The right to health is one of human rights, therefore the state should guarantee every citizen to get good health care and quality. Social Security Agency (BPJS) Health is one of the country's efforts in fulfilling the right to health. Through this paper the authors wanted to know how the right to health is done by BPJS Health and Health BPJS obstacles encountered in providing adequate health insurance for the community. BPJS Health in carrying out the duties and functions must be able to ensure the availability, accessibility, acceptability and quality of health services is inadequate. Constraints that are regulatory, administrative and technical BPJS Health inhibit performance. Therefore, it is necessary to encourage improvements to all Indonesian people can participate and benefit from the existence BPJS Health.